Isoflavon. Berbagai sumber, sifat, dan manfaatnya pada penyakit degeneratif - WINARSI, Hary (Gadjah Mada University Press, 2005)
Isioflavon. Berbagai sumber, sifat, dan manfaatnya pada penyakit degeneratif